Appetite for Reform: When do Exogenous Shocks Motivate Industrial Policy Change?. Issue 6 (3rd June 2022) - Fuentes, Alberto; Pipkin, Seth
Abstract: Although much industrial policy research addresses the "supply side' task of discerning superior policies, it pays less attention to 'demand side' questions of when and to what extent countries adopt reforms. And while exogenous shocks serve as the impetus for new industrial policy adoption across a broad array of empirical case studies, less is known about when such shocks register as salient enough to elicit policy shifts. This paper considers the conditions under which exogenous shocks motivate varying degrees of industrial policy change. We examine divergent reforms in Mexico and Brazil's petroleum industries after the 1973 Oil Shock, and automotive industries following the 1982 Debt Crisis. The evidence informs a 'satisficing' model, which suggests that the interaction between exogenous shocks and two main local factors – the 'goals' of a paradigm shared by industry decision-makers, and the aggregate levels of 'slack' resources available to quell dissent in times of uncertainty – shapes varying orders of policy response. This satisficing model proves useful in anticipating how responses to external crises might unfold at the industry level.